Asia-Pacific Fishing Livelihoods 2021
DOI: 10.1007/978-3-030-79591-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Fishing Livelihoods and Social Diversity

Abstract: This chapter shifts scale from Chap. 10.1007/978-3-030-79591-7_2 to focus on the local context and analyse the everyday sets of social relationships that frame the lives of those engaged in fishing livelihoods. The broad structural forces of migration, technology and markets along with the wider economy all intersect with local sets of social structures to shape the conditions in which fishing livelihoods operate. Here we present two examples of how different forms of social differentiation interact with fishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Therefore, fish vending activities significantly improved the livelihoods of women fish vendors. The study of Fabinyi and Barclay (2021) support this finding by stating that women fish vendors enter the vending industry due to financial hardship and thus it contributes to the family's financial capital.…”
Section: Financial Capitalmentioning
confidence: 86%
See 2 more Smart Citations
“…Therefore, fish vending activities significantly improved the livelihoods of women fish vendors. The study of Fabinyi and Barclay (2021) support this finding by stating that women fish vendors enter the vending industry due to financial hardship and thus it contributes to the family's financial capital.…”
Section: Financial Capitalmentioning
confidence: 86%
“…The study by Azmi and Lundi (2022) showed that a severe lack of medical facilities and other infrastructure affected the activities of fishing communities in Bangladesh in reducing their income. In another case, Fabinyi and Barclay (2021) emphasized that the physical infrastructure provided by the authorities is affected by livelihood improvement while improving the welfare of the people.…”
Section: Empirical Literature the Role Of Fish Vending On Livelihoodsmentioning
confidence: 99%
See 1 more Smart Citation